A WITTGENSTEINIAN’ DISSOLUTION OF THE FUNDAMENTALS’ METAPHOR (Andamios, Revista de Investigación Social, 2011)
This article defends a conception of epistemic normativity and linguistic justification from a wittgensteinian point of view. The author recuperates the relevance of social practices and the social character of language for the processes of justification of beliefs and to give an account of that which makes the use of terms significant.
Keywords: Normativity; epistemological justification; skepticism; foundationism